Click to save and return to course: online education, adjunctification, and the disciplining of academic labour. (1st April 2017) - ,
Abstract : There has been little analysis of how neoliberal adjunctification and online education (OLE) are shaping a new academic division of labour in US colleges and universities. OLE rationalises academic labour by separating it from the delivery of educational content while transforming learning into the self-disciplined completion of sequential tasks (e.g. 'competency-based learning') under the panoptic surveillance of online course management systems (CMS). OLE is subtly shifting the very hidden curriculum of higher education to meet the needs of global capital for a more effectively disciplined labour force that can work contingently and remotely with little or no overt coercion. This analysis of the process by which OLE is rationalising academic labour draws upon the ideas of Foucault and Tronti to argue that OLE is a tool for producing a type of disciplined labour that breaks down the borders between productive and reproductive labour in order to colonise all life as work.